If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -30 = 56 + -49x Reorder the terms: -30 + 3x = 56 + -49x Solving -30 + 3x = 56 + -49x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '49x' to each side of the equation. -30 + 3x + 49x = 56 + -49x + 49x Combine like terms: 3x + 49x = 52x -30 + 52x = 56 + -49x + 49x Combine like terms: -49x + 49x = 0 -30 + 52x = 56 + 0 -30 + 52x = 56 Add '30' to each side of the equation. -30 + 30 + 52x = 56 + 30 Combine like terms: -30 + 30 = 0 0 + 52x = 56 + 30 52x = 56 + 30 Combine like terms: 56 + 30 = 86 52x = 86 Divide each side by '52'. x = 1.653846154 Simplifying x = 1.653846154
| 4x+9=-3x-12 | | f(x)=-2x^2+4x-3 | | 28-15k=17 | | 4x-8=7x+16 | | 12=3-(5+b) | | (a+3)(a-4)=0 | | 8=(r+4) | | x-10=7(24-21x) | | 22-ln(2-x)=0 | | 6(2x-3)=3(3-5) | | 10x+12y=2244 | | -6(2-5x)=-102 | | f(x)=x^2-6x-4 | | 5t=88 | | 5=3x^2-7x+11 | | (7x^2+12)-(9x^2-2)= | | -8x+45=45-8x | | -6(2-5x)=102 | | 2-(3-a)=-4 | | X+3x=110 | | 13x+2=4r+38 | | 20=1+6ln(5x+1) | | 4(u+2)=-6u-42 | | 2(x-100)=80 | | 8(-9-4a)-6(3a-5)= | | 21t-21=21 | | -9p+1+7p-10= | | x-10 = 7 (8-7x)3 | | 4x^2+61x=5701 | | (7x^2+12)-(9x^2-2)=y | | 4.8e^3=x | | 4-21x=19 |